Forest Soils Properties and Management - Osman, Khan Towhid; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2013)
Forest soil characteristics are not only unique but their interpretation also differs from cropland soils. Just as there are diverse forest types, there are many soil variants that need different management. Today, forest plantations are being intensively managed for profitable timber, pulpwood and energy production. Site selection, species selection, site productivity evaluation, silvicultural treatments, and soil amendments need crucial soil information.   This book provides a comprehensive overview of the physical, chemical and biological properties of forest soils and their implications on forest vegetation. Topics discussed include:   ·         major forest types of the world and their associated soils ·         forest biomass and nutrient dynamics ·         organic matter turnover and nutrient recycling ·         forest soil disturbance ·         forest soil and climate change ·         forest soil management and silvicultural treatments   The text leads the reader from the basics to a comprehensive understanding of forest soil science.  Study questions at the end of each chapter help to reinforce concepts.   While the text will be of particular interest to undergraduate students in grasping the fundamentals, it will also be of interest to graduate students and professionals in forestry, agroforestry and soil science, including those involved in nursery operations and plantation management.
Rocks, Minerals and Soils -- Physical Properties of Forest Soils.-  Chemical Properties of Forest Soils,- Organic Matter of Forest Soils -- Biological Properties of Forest Soils -- Nutrient Dynamics in Forest Soil -- Forest Types and Their Associated Soils -- Forest Disturbances and Soil Degradation -- Forest Soil and Climate Change -- Objectives of Forest Soil Management -- Index.
Keywords: Forestry; Soil science; Soil conservation; Earth sciences; Forestry management; Environmental management; Forestry; Soil Science & Conservation; Earth Sciences, general; Forestry Management; Environmental Management